ABC Helpful Me : Learn all the ways you can be a helper -- from A to Z! - Harrison, Erica (Beverly, MA : Walter Foster Jr., an imprint of the Quarto Group, 2022)
When we help ourselves and help each other, we make our communities and the world a better place. From A to Z, here are 26 things that you can do to help out in big and small ways!
Keywords: English language -- Alphabet -- Juvenile literature; Helping behavior -- Juvenile literature; Board books; Picture books